1974
DOI: 10.3758/bf03332990
|View full text |Cite
|
Sign up to set email alerts
|

Lateral hypothalamic self-stimulation: Effect of excess body weight

Abstract: Self-stimulation in the lateral hypothalamus was measured in rats made obese by force-feeding a liquid diet. Mean self-stimulation rate at the obese weight was significantly less than the mean self-stimulation rate at normal weight levels. This result is consistent with the view that a factor correlated with obesity inhibits feeding by inhibiting lateral hypothalamic reward.Obesity inhibits feeding. Rats that have been forced to become obese, by force-feeding, insulin treatments, or lateral hypothalamic stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Olds, 1977; Rolls, 1975). These models are consistent with the following observations: (a) Many procedures that decrease food intake also decrease the rate of self-stimulation at lateral hypothalamic sites (Balagura, 1968; Balagura & Hoebel, 1967; Hoebel, 1968; Hoebel & Teitelbaum, 1962; Hoebel & Thompson, 1969; Huston, 1971; Kornblith & Hoebel, 1976; MacNeil, 1974; Mount & Hoebel, 1967). (b) Both species-typical eating and/or drinking (Cox & Valenstein, 1969; Roberts, 1980) and reinforcement effects (Goldstein, Hill, & Templer, 1970; Mogenson, 1969; J.…”
supporting
confidence: 90%
“…Olds, 1977; Rolls, 1975). These models are consistent with the following observations: (a) Many procedures that decrease food intake also decrease the rate of self-stimulation at lateral hypothalamic sites (Balagura, 1968; Balagura & Hoebel, 1967; Hoebel, 1968; Hoebel & Teitelbaum, 1962; Hoebel & Thompson, 1969; Huston, 1971; Kornblith & Hoebel, 1976; MacNeil, 1974; Mount & Hoebel, 1967). (b) Both species-typical eating and/or drinking (Cox & Valenstein, 1969; Roberts, 1980) and reinforcement effects (Goldstein, Hill, & Templer, 1970; Mogenson, 1969; J.…”
supporting
confidence: 90%
“…Hoebel and Teitlebaum (1962) and Margules and Olds (1962) reported that electrodes placed in the LH that induced stimulus-bound feeding also supported high rates of responding for intracranial selfstimulation (ICS). Hypothalamic sites that regulate feeding thus seem to exert a corresponding control & Hoebel, 1967;Wilkinson & Peele, 1962), whereas decreases follow gastric distension (Hoebel, 1968;Hoebel & Thompson, 1969;MacNeil, 1974). Hoebel (1968) found these decreases in self-stimulation rates regardless of whether the distension was produced by intragastric feeding or by the inflation of a gastric balloon.…”
Section: Iowa State University Ames Iowa 50010mentioning
confidence: 99%